Degradation of Malachite Green on MoS2/TiO2 Nanocomposite - Hu, Kun-Hong; Meng, Mian (Asian Journal of Chemistry, 2013)
The catalytic activity of a MoS2/TiO2 nanocomposite was evaluated using the degradation reaction of malachite green. The MoS2/TiO2 nanocomposite revealed excellent photocatalytic activity in the degradation reaction of malachite green. The good catalytic activity of the MoS2/TiO2 nanocomposite was ascribed to the large BET surface area. The degradation rate of malachite green was affected by reaction conditions, such as initial concentration of malachite green, repeatedly used cycles and dosage of MoS2/TiO2 nanocomposite. It is suggested that the MoS2/TiO2 nanocomposite was a promising catalyst for the removal of malachite green.